Hyperhomocysteinemia in Patients with Hypothyroidism (Medical Forum Monthly, 2021)
Objective: To determine the hyperhomocysteinemia in patients with hypothyroidism.Study Design: Cross Sectional Descriptive StudyPlace and Duration of Study: This study was conducted at the Liaquat University Hospital Hyderabad from January 2018 to December 2018.Materials and Methods: The inclusion criteria were the patients of age ≥18 year, either gender and aged 18 years and newly diagnosed case of hypothyroidism (TSH >15mU/l) while the exclusion criteria were the patients with <18yrs, already on thyroid replacement therapy and vitamin B12 and folic acid, the subjects with subclinical hypothyroidism, the individuals who developed hypothyroidism as a result of thyroidectomy or radioablation, the patients already on phenytoin, phenobarbitone and valproate, niacin and cholestyramine. The relevant and specific investigations were advised and 2 ml venous blood was taken after aseptic measure and sent to laboratory for serum homocysteine level. The frequency and percentages were computed for categorical variables whereas the mean ± SD was computed for numerical variables.Results: During one-year study period total fifty patients with hypothyroidism were recruited and studied had mean age ± SD identified as 47.87±7.52 (yrs) with female gender predominance 34 (68%). Regarding residence, the urban and rural population was identified as 22 (44%) and 28 (56%) while the clinical features observed were weight gain 42 (84%), fatigue 30 (66%), puffiness of face 28 (56%), leg swelling 23 (46%), cold intolerance 18 (36%). the hyperlipidemia was observed in 30 (60%) while the other comorbities observed were diabetes mellitus 35 (70%), hypertension 28 (56%), obesity 23 (46%), osteoporosis 21 (42%) whereas the hyperhomocysteinemia was observed in 32 (64%) patients respectively.Conclusion: The patients with hypothyroidism are at risk for hyperhomocysteinemia and dyslipidaemia and are more prone to premature atherosclerosis and increased adverse cardiovascular events.